Performance analysis of QoS scheme supported in MIPV6 network - Hussein, Loay Faisal; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi (IDOSI Publication, 2013)
The contemporary Internet that we have been using today is based on Best-Effort (BE) service only, where packets are assigned and forwarded with the same priority. The BE service is acceptable only for traditional Internet applications like e-mail, web browsing and file transfer. However, it is not adequate for the applications like video conferencing, voice over IP (VoIP) and video on demand (VoD), which require high bandwidth, low delay and delay variation. Obviously, with the emergence of new real-time applications and Quality of Service (QoS) requirements, the Best Effort service becomes insufficient. Therefore, the Internet community has developed a number of new technologies to provide QoS in the Internet such as IntServ, DiffServ and MPLS. The differentiated service (DiffServ) is the most important distinct technology due to its simplicity and scalability benefits. It has been endorsed by Internet Engineering Task Force (IETF) to satisfy the requirements of new real-time applications. Internet Protocol was not designed taking into account mobility of users and terminals. In few years later, the IETF has developed protocols such as Mobile IPv4 (MIP) and Mobile IPv6 (MIPv6) for supporting seamless connectivity to mobile hosts. Mobile IPv6 is considered one of the important host mobility protocols, which was defined more in (RFC 3775 and RFC 6275). This paper acquaints with analytical analysis for the previously proposed scheme (DiffServ-MIPv6) that applies the DiffServ methodology techniques to Mobile IPv6 network in order to suit the needs of both QoS guaranteed and mobility in communication. The analytical study is investigated to evaluate the performance of the proposed scheme (DiffServ-MIPv6) compared to the native standard MIPv6 protocol in terms of signaling cost. The numerical results are measured against two factors, binding lifetime period and wireless link delay as well. Key words: Quality of Service DiffServ Mobile IPv6